Aplikasi sistem informasi perpustakaan Mbaku (Mari Baca Buku) - Sutikman, Sutikman; Winarsih, Winarsih (Jurnal Tika, 2022)
Books are a medium for anyone to gain knowledge or dig up information, especially for students. In the learning process, students are often asked to look for references and additional information through books. In the process, of course, the campus provides book lending facilities, namely the library. However, it is often found that the books needed when searched for in the library directly are not available or the stock is inadequate so that it wastes the user's time to come and search in the library with the probability of getting the book that meets expectations is only 50%. Mari Baca Buku (MBAKU) is a web-based application that is used by users to search for information related to books online by getting certainty about the validity of the desired book data before carrying out the process of borrowing books at the library. MBAKU application provides solutions related to the problem of book stock and bridges between one library to another, thus providing access for MBAKU members to be able to borrow books at several libraries in Indonesia that have been integrated with MBAKU. The stages of designing this application include system design, use case design and activity diagrams, database design and interface design design. The database used is MySQL while the programming language uses PHP 7 and TypeScript. The result is a library information system application with all available features and has two user levels and has its own access rights. The two user levels are the user and the administrator.